Common Variable Immunodeficiency and Autoimmune Diseases: A Retrospective Study of 95 Adult Patients in a Single Tertiary Care Center - Mormile, Ilaria; Punziano, Alessandra; Riolo, Carlo Alberto; Granata, Francescopaolo; Williams, Michela; de Paulis, Amato; Spadaro, Giuseppe; Rossi, Francesca Wanda (Frontiers in Immunology, 2021)
Common variable immunodeficiency (CVID) is the most common clinically significant primary immunodeficiency in adulthood, which presents a broad spectrum of clinical manifestations, often including non-infectious complications in addition to heightened susceptibility to infections. These protean manifestations may significantly complicate the differential diagnosis resulting in diagnostic delay and under-treatment with increased mortality and morbidity. Autoimmunity occurs in up to 30% of CVID patients, and it is an emerging cause of morbidity and mortality in this type of patients. 95 patients (42 males and 53 females) diagnosed with CVID, basing on ESID diagnostic criteria, were enrolled in this retrospective cohort study. Clinical phenotypes were established according to Chapel 2012: i) no other disease-related complications, ii) cytopenias (thrombocytopenia/autoimmune hemolytic anemia/ neutropenia), iii) polyclonal lymphoproliferation (granuloma/lymphoid interstitial pneumonitis/persistent unexplained lymphadenopathy), and iv) unexplained persistent enteropathy. Clinical items in the analysis were age, gender, and clinical features. Laboratory data included immunoglobulin (Ig)G, IgM and IgA levels at diagnosis, flow-cytometric analysis of peripheral lymphocytes (CD3+, CD3+CD4+, CD3+CD8+, CD19+, CD4+CD25highCD127low, CD19hiCD21loCD38lo, and follicular T helper cell counts). Comparisons of continuous variables between groups were performed with unpaired t-test, when applicable. 39 patients (41%) showed autoimmune complications. Among them, there were 21 females (53.8%) and 18 males (46.2%). The most prevalent autoimmune manifestations were cytopenias (17.8%), followed by arthritis (11.5%), psoriasis (9.4%), and vitiligo (6.3%). The most common cytopenia was immune thrombocytopenia, reported in 10 out of 95 patients (10.5%), followed by autoimmune hemolytic anemia (n=3, 3.1%) and autoimmune neutropenia (n=3, 3.1%). Other autoimmune complications included thyroiditis, coeliac disease, erythema nodosum, Raynaud's phenomenon, alopecia, recurring oral ulcers, autoimmune gastritis, and primary biliary cholangitis. There were no statistically significant differences comparing immunoglobulin levels between CVID patients with or without autoimmune manifestations. There was no statistical difference in CD3+, CD8+, CD4+CD25highCD127low T, CD19, CD19hiCD21loCD38lo, and follicular T helper cell counts in CVID patients with or without autoimmune disorders. In conclusion, autoimmune manifestations often affect patients with CVID. Early recognition and tailored treatment of these conditions are pivotal to ensure a better quality of life and the reduction of CVID associated complications.